2021
DOI: 10.1371/journal.pone.0253141
|View full text |Cite
|
Sign up to set email alerts
|

Facial expressions of Asian people exposed to constructed urban forests: Accuracy validation and variation assessment

Abstract: An outcome of building sustainable urban forests is that people’s well-being is improved when they are exposed to trees. Facial expressions directly represents one’s inner emotions, and can be used to assess real-time perception. The emergence and change in the facial expressions of forest visitors are an implicit process. As such, the reserved character of Asians requires an instrument rating to accurately recognize expressions. In this study, a dataset was established with 2,886 randomly photographed faces f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…This is in accordance with findings that happy scores had a negative relationship with sad scores. Photos of unaware pedestrians did not show any differences between male adolescents and other groups of visitors in urban forest parks [29,39]. However, an enormous survey interviewing 200,000 teenagers from 42 European countries also suggested that male adolescents looked happier than female adolescents [47].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with findings that happy scores had a negative relationship with sad scores. Photos of unaware pedestrians did not show any differences between male adolescents and other groups of visitors in urban forest parks [29,39]. However, an enormous survey interviewing 200,000 teenagers from 42 European countries also suggested that male adolescents looked happier than female adolescents [47].…”
Section: Discussionmentioning
confidence: 99%
“…Gender was categorized into female and male according to visual perceptions of sexual characteristics. Age was categorized into five ranges: toddler (1-5 years-old), adolescent (6-19 years-old), youth (20-25 years-old), middle-aged (35-50 years-old), and senior (over 60 years-old) [39,40].…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because, for example, in the circumplex affect model, the surprise is neutral in valence but not in arousal (Russell & Barrett, 1999). Moreover, a recent study on facial expressions reported that surprised and neutral faces were mapped separately (Guan, Wei, Hauer, & Liu, 2021). Therefore, we avoided claims about neutral emotions in surprised faces.…”
Section: Replymentioning
confidence: 99%
“…To date, automated facial expression recognition has rarely been used in environmental psychology research. In a series of experiments conducted by Wei and his colleagues [ 25 , 26 , 40 , 41 ], participants were asked to take selfies or were photographed while walking on urban streets or in a forest park. The photographs were analyzed using FireFACE software.…”
Section: Introductionmentioning
confidence: 99%